Closing the value-based circle in shared decision-making: a digital framework for informing the shared decision-making process through patient reported outcome and experience measures - del Olmo Rodríguez, Marta; Martos Martinez, Rafael; Pascual Martínez, Adriana; Miranda Castillo, Carolina; Short Apellaniz, Jorge; Pfang, Bernadette; Baca-García, Enrique; Córdoba Mascuñano, Raúl (Frontiers in Public Health, 2024)
Background The spreading adoption of value-based models of healthcare delivery has incentivized the use of patient-reported outcomes and experience measures (PROMs and PREMs) in clinical practice, with the potential to enrich the decision-making process with patient-reported data. Methods This perspective article explores PROs and the shared decision-making (SDM) process as components of value-based healthcare. We describe the potential of PROMs and PREMs within the decision-making process and present a digital framework for informing the shared decision-making process using aggregated data from a healthcare system PROMs and PREMs program, including early results from implementation in hospital network in Madrid, Spain. Results The proposed digital framework incorporates aggregated data from a hospital network PROMs and PREMs program as part of a digital patient decision aid (PDA) for patients with lymphoma. After the first hematologist appointment, participating patients access the PDA to review relevant information about clinical and patient-reported outcomes for each of the possible options, assign a personal order of priority to different outcomes, and then select their preferred course of action. Patients’ answers are automatically uploaded to the EHR and discussed with hematologists at the next appointment. After beginning treatment, patients are invited to participate in the network PROMs program; participants’ PROMs data are fed back into the PDA, thus “closing the circle” between the decision-making process and patient-reported data collection. During the first 14 months after launching the decision aid in October 2022, of 25 patients diagnosed with follicular lymphoma at the four participating hospitals, 13 patients decided to participate. No significant differences in age or sex were observed between groups. Average SDM Q-9 score for patients filling in the questionnaire (n = 6) was 36.15 of 45 points. Conclusion Various obstacles toward widespread implementation of SDM exist such as time constraints, lack of motivation, and resistance to change. Support and active engagement from policy makers and healthcare managers is key to overcome hurdles for capturing patient-reported data and carrying out shared decision-making at healthcare system level. Early results of a digital framework for PRO-enriched SDM seem to be beneficial to the decision-making process.